In situ chromatin interactomics using a chemical bait & trap approach - Burton, Antony J. (Nat Chem, 2020)
Elucidating the physiological binding partners of histone post-translational modifications (hPTMs) is key to understanding fundamental epigenetic regulatory pathways. Determining such interactomes will enable the study of how perturbations of these interactions affect disease. Here we use a synthetic biology approach to set a series of hPTM-controlled photo-affinity traps in native chromatin. Using quantitative proteomics, the local interactomes of these chemically customized chromatin landscapes are determined. We show that the approach captures transiently interacting factors such methyltransferases and demethylases, as well as previously reported and novel hPTM reader proteins. We also apply this in situ proteomics approach to a recently disclosed cancer-associated histone mutation, H3K4M, revealing a number of perturbed interactions with the mutated tail. Collectively our studies demonstrate that modifying and interrogating native chromatin with chemical precision is a powerful tool for exploring epigenetic regulation and dysregulation at the molecular level.